INOVASI PENDIDIKAN ISLAM DI INDONESIA DAN MALAYSIA (LITERATUR REVIEW) - Kurnia Julianti; Agus Setiawan; H. Ahmad Nordian (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2021)
Abstract The quick improvement of the ongoing nearby, territorial and global climate has suggestions for the administration of instruction at each degree of existing schooling. Innovations in education must be used to raise the quality of education to counteract these changes. In Indonesia and Malaysia, the politics that overshadow Islamic education are inseparable from innovation. These politics play a significant role in modifying the curriculum, starting with the government system. Findings from the history of Indonesian and Malaysian education research; Between the Ulama education system and the colonialist-introduced western education system, the educational system experienced dualism. Changes in curriculum that have occurred in Indonesia and Malaysia since they were colonized and gained independence cannot be separated from a curriculum that is geared toward the West. Keyword: innovation, Islamic education. Abstrak Peningkatan cepat dari iklim lokal, teritorial dan global yang sedang berlangsung memiliki saran untuk administrasi pengajaran di setiap tingkat sekolah yang ada. Inovasi dalam pendidikan harus digunakan untuk meningkatkan kualitas pendidikan untuk menangkal perubahan tersebut. Di Indonesia dan Malaysia, politik yang menaungi pendidikan Islam tidak lepas dari inovasi. Politik ini memainkan peran penting dalam memodifikasi kurikulum, dimulai dengan sistem pemerintahan. Temuan dari sejarah penelitian pendidikan Indonesia dan Malaysia; Antara sistem pendidikan Ulama dan sistem pendidikan barat yang diperkenalkan oleh kolonialis, sistem pendidikan tersebut mengalami dualisme. Perubahan kurikulum yang terjadi di Indonesia dan Malaysia sejak dijajah dan merdeka tidak lepas dari kurikulum yang bermuara pada Barat. Kata Kunci: inovasi, pendidikan Islam